Nursing Students’ Knowledge And Attitude Toward Covid-19 - Syahruramdhani; Khasanah, Azizah Nur (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction: Coronavirus disease (COVID-19) is an infectious disease caused by a coronavirus that is transmitted from person to person and has become a worldwide pandemic outbreak. Health college students go directly to the front line in health services and play an active role in following developments in health problems such as good knowledge and good attitudes that can help prevent the spread of COVID-19. Purpose: The purpose of this study was to determine the relationship between nursing students' knowledge and attitudes towards the prevention of COVID-19 infection. Method: This study uses a quantitative method with correlation. Sampling used a cluster random sampling technique with a population of 218 college students from the school of nursing, Universitas Muhammadiyah Yogyakarta. Result: The results showed that the knowledge nursing students about COVID-19 had a good category of 99 (45.4%), the attitudes of PSIK UMY nursing students regarding prevention of COVID-19 had a good category of 191 (87.6%), and the results of the Spearman Rho test were a p-value of 0.000. Conclusion: This study proves that there is a strong relationship between students' knowledge and attitudes towards COVID-19.